A study on understanding the contents of word-of-mouth communication and the corresponding nonverbal behaviour. - Tan, Chor Howe. (2008)
The analysing and understanding of word-of-mouth communication and its contents. The study will look at the relationship of the WOM given in different positive and negative product or service experiences. An area of WOM that is relatively unexplored by WOM researchers – that of nonverbal behaviour complementing WOM is also explored.